How and why pharmaceutical reforms contribute to universal health coverage through improving equitable access to medicines: a case of Ghana - Koduah, Augustina (Frontiers in Public Health, 2023)
Examining how and why a country prioritizes and implements pharmaceutical reforms tends to show myriad efforts made toward improving access to medicines. This paper examines factors that enabled the prioritization and implementation of selected pharmaceutical reform items and how these contributed to improving equitable access to medicines and universal health coverage in Ghana.An analytical framework was developed, to identify variables to explore in answering the study questions and frame the analysis and presentation of findings. Documents analyzed included the national medicines policies, health sector program of work, and other health policies.Quantitative data was sourced from databases maintained by World Health Organization and the Institute for Health Metrics and Evaluation.Three main factors: evidence, financial and technical support, and alignment to national and global policies influenced the prioritization and implementation of access to medicines reforms. The reforms targeted rational selection and use of medicines, medicines pricing, sustainable medicine financing, and regulatory and supply chain systems. Although there was limited quantitative data to quantify access to medicines policies' impact on universal health coverage, it can be reasonably assumed that in Ghana, access to medicines policies have contributed to financial protection and improved access to quality health service.Access to medicines policies targeted at promoting rational medicine selection and use, regulating medicines pricing, improving sustainable medicines financing, and the regulatory and supply chain systems arguably contributed to the attainment of UHC and must be sustained. Data collection and reporting indicators for access to medicines must be prioritized.